Combining the good tribological properties with the high adhesion strength of the amorphous carbon films in situ grown on PI - Wu, Yutao; Wang, Yongxin; Li, Yue (Frontiers in Materials, 2023)
Polyimide (PI) is widely utilized in the modern industry because of its excellent heat resistance, dielectric properties, radiation resistance and chemical stability, but its low hardness and poor wear resistance limit its service life. In this experiment, we treated polyimide surfaces with carbon plasma to prepare the amorphous carbon films with in-situ transition layers. The microstructure, mechanical properties and tribological properties of the amorphous carbon films were studied. The results showed that the hardness and wear resistance of the PI surface were greatly improved by the amorphous carbon film with in-situ transition layer. More importantly, the in-situ transition endowed the film high adhesion strength on the PI substrate. The roles of the carbon plasma in the deposition process of the amorphous carbon, namely the deposition effect, and the induction effect, referring to the effect on the top layer of PI substrate, were systematically analyzed. This work realizes the purpose of protecting the PI surface with the amorphous carbon film with high adhesion strength, and also provides a new idea for improving the adhesion between hard coating and flexible substrate.